2005
DOI: 10.1158/1055-9965.epi-04-0468
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Type of Cigarette on Peripheral versus Central Lung Cancer

Abstract: Objectives: Adenocarcinoma has replaced squamous cell carcinoma as the most common cell type of lung cancer in the United States. It has been proposed that this shift is due to the increased use of filter and lower-tar cigarettes, resulting in increased delivery of smoke to peripheral regions of the lungs, where adenocarcinoma usually occurs. We reviewed radiologic data to evaluate the hypothesis that tumors in smokers of cigarettes with lower-tar yield are more likely to occur peripherally than tumors in smok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
54
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 41 publications
(61 reference statements)
1
54
0
Order By: Relevance
“…On the basis of the site of the primary cancer, squamous cell lung cancer is described as central (CSCCa) or peripheral (PSCCa). The incidence of PSCCa is increasing and is reported to be approximately 50% of squamous cell lung cancer (3)(4)(5)(6). Although the etiology of squamous cell lung cancer is not known, smoking and chronic lung inflammation have been recognized as predisposing factors (7).…”
mentioning
confidence: 99%
“…On the basis of the site of the primary cancer, squamous cell lung cancer is described as central (CSCCa) or peripheral (PSCCa). The incidence of PSCCa is increasing and is reported to be approximately 50% of squamous cell lung cancer (3)(4)(5)(6). Although the etiology of squamous cell lung cancer is not known, smoking and chronic lung inflammation have been recognized as predisposing factors (7).…”
mentioning
confidence: 99%
“…[13] In their study, Watanabe et al [14] showed that the majority of the histological types of peripheral tumors were adenocarcinomas. In a study by Brooks et al, [15] the frequency of SCCs was found to be increasing in central tumors. In our study, SCC was seen more than adenocarcinoma in endobronchial tumors (85.6% vs. 9.8%) and the difference in between was statistically significant.…”
Section: Discussionmentioning
confidence: 90%
“…Another reason is that epidemiological studies show no overall evidence of any increase in the risk of AdC associated with filter vs. plain or lower vs. higher tar cigarettes [5,[9][10][11][12]. Low tar filter cigarettes are associated with a small reduction in risk of SqCC, but not enough to explain the observed large rise over time in the frequency of AdC relative to SqCC.…”
mentioning
confidence: 97%
“…The argument that the switch to lower tar filtered cigarettes from the older, higher tar, plain cigarettes has been responsible for the rise in the incidence of adenocarcinoma (AdC) and in the ratio of AdC to squamous cell carcinoma (SqCC) is one that has been made previously on various occasions, [2][3][4] and has been supported by various researchers [5,6].…”
mentioning
confidence: 99%